Characterization of Key Odorants in Moroccan Argan Oil by Aroma Extract Dilution Analysis. Issue 5 (8th April 2019) - Sevindik, Onur; Amanpour, Asghar; Tsouli Sarhir, Salwa; Kelebek, Hasim; Selli, Serkan
Abstract : The aroma‐active compounds of Moroccan argan oil are sensorily and instrumentally analyzed via gas chromatography‐mass spectrometry‐olfactometry (GC‐MS‐O). The purge and trap extraction (PTE) method is used for the extraction of volatile components. A total of 35 aroma compounds are determined including mostly alcohols and pyrazines, and some carboxylic acids, pyrroles, furans, lactones, volatile phenols, an aldehyde, and a ketone. An aroma extract dilution analysis of the aromatic fraction of argan oil isolated by the PTE method reveals 19 key odorants with flavor dilution (FD) factors ranging from 4 to 512, among which nonanal, 2, 5‐dimethyl‐3‐ethylpyrazine and 2, 3‐diethyl‐5‐methylpyrazine show the highest FD factors of 512. As for the principal scents perceived by all panelists, characteristic odor notes in argan oil are found to be roasty, nutty, fatty, earthy, and cheesy. Practical Applications : Nut oil is one of the most widely consumed oils in many countries. The outcomes of this investigation provide valuable information for elucidation of the key odorants and aroma composition of the well‐known and expensive Moroccan argan oil. Aroma is a crucial quality parameter of a foodstuff which directly influences customer preferences. Therefore, determining the key odorants of argan oil's aromatic extract isolated by purge and trap methodology is of major importance for the argan oil sector. The purge and trap extraction set for separation followed by analysis and characterization of those compounds via gas chromatography–mass spectrometry‐olfactometry (GC‐MS‐O) is an effective practical application tool for aroma description in valuable and expensive oil samples. It is observed that the characteristic odor notes of argan oil are related to the few most powerful aroma‐active compounds using the aroma extract dilution analysis technique. The aroma‐active compounds of Moroccan argan oil are sensorily and instrumentally analyzed via gas chromatography‐mass spectrometry‐olfactometry (GC‐MS‐O). The purge and trap extraction (PTE) method is used for the extraction of volatile components. A total of 19 aroma compounds are detected as aroma active by AEDA method among 35 volatiles. Characteristic odor notes in argan oil are found to be roasty, nutty, fatty, earthy, and cheesy. Abstract : The aroma‐active compounds of Moroccan argan oil are sensorily and instrumentally analyzed via gas chromatography‐mass spectrometry‐olfactometry (GC‐MS‐O). The purge and trap extraction (PTE) method is used for the extraction of volatile components. A total of 19 aroma compounds are detected as aroma active by AEDA method among 35 volatiles. Characteristic odor notes in argan oil are found to be roasty, nutty, fatty, earthy, and cheesy.